Discerning the success of sustainable planning: A comparative analysis of urban heat island dynamics in Korean new towns. (October 2020) - Kwak, Yoonshin; Park, Chan; Deal, Brian
Highlights: Urban structures have a notable effect on the patterns and intensities of heat island effect (UHI). Green and blue space ratios, road networks, and housing distributions affect UHI significantly. Sustainable urban development policies in Korea lead less aggravated UHIs. Spatial-temporal management is necessary because UHI is aggravated during development. Abstract: UHI is an important measure for understanding the urban landscape, especially in terms of thermal agglomeration and disturbance. This research aims to discern the success of sustainability planning by examining and comparing the different characteristics of UHIs through the combination of machine learning and statistical methods. To achieve this, we analyze 4 new towns in Korea, which include two 'old' new towns and two 'recent' new towns. The key difference between our test towns lies on whether or not the sustainability policies were applied to their development plans. We visualize LST and conduct a k -mean clustering to find and quantify spatial patterning in the resulting UHI measures. We then compare the statistical relations between LST and 6 UHI driven variables across the towns. Using comparative analysis, this research reveals that sustainable development policies have a notable effect on the patterns and intensities of UHI. Urban structures, planned under development policies, including green and blue space ratios, road networks, and housing distributions, were found to affect UHI significantly. We quantifiably confirm that the sustainability policies implemented in planning the 'recent' new towns allow the towns to experience less aggravated UHIs than the 'old' new towns. However, we also claim a need to develop appropriate, long-term UHI management regulations for the 'recent' new towns. This paper provides a solid basis for improving Korean new town planning and managing the environmental issues in urban systems for planners, designers, and decision-makers to establish the sustainable built environment.